ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG IKAN DI KELURAHAN KEDONGANAN - I Ketut Sudibia, Ngakan Putu Widnyana Putra, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Kedonganan is designated as one of the biggest fisheries and marine business centers in Bali and has two markets that specifically sell fish and other marine products. But local people have been reluctant to work in the fisheries sector both as fishermen and traders. The objectives to be achieved in this study are: 1) To analyze the effect of capital, length of business, migration status, and simultaneous working hours on income of fish traders in Kedonganan Village. 2) To analyze the effect of capital, length of business, migration status, and working hours partially on the income of fish traders in Kedonganan Village. The sample of this study was 140 respondents and used multiple linear regression analysis techniques. The results of data analysis showed that 1) capital, length of business, migration status, and working hours had a simultaneous and significant effect on the income of fish traders in Kedonganan Village. 2) Capital has a positive effect on the income of fish traders in Kedonganan Village. 3) The duration of the business has a positive effect on the income of fish traders in Kedonganan Sub-District 4) The status of migration has no significant effect on the income of fish traders in Kedonganan Sub-District. 5) Working hours have a positive effect on the income of fish traders in Kedonganan Village.